International Tourism and Infectious Disease Transmission Nexus: A Cross-Country and Regional Study. (November 2022) - Selvanathan, Eliyathamby A.; Jayasinghe, Maneka; Selvanathan, Saroja
The relationship between pandemics and travel is an essential element in understanding health security and global change. Using cross-country COVID-19 confirmed cumulated cases and deaths data for 165 countries as of 3rd February 2021, this study investigates the impact of tourism, the experience of SARS and Swine flu, and several other socio-economic variables on the spread of the COVID-19 pandemic at the global and regional level. The results reveal that (1) the higher the volume of inbound and outbound tourism, the higher the number of reported COVID-19 cases and deaths at the global as well as at the regional level; (2) the impact of tourism on COVID-19 cases and deaths varies across regions, and; (3) countries that have experience in handling SARS or Swine flu pandemics have been able to reduce COVID-19 cases and deaths significantly, in particular, the countries in the Asia Pacific region.